Narsisme Direktur, Komposisi Komisaris Independen dan Gender Direktur Pada Kualitas Laporan Keuangan BUMN - Syukra, Rahmiyatus; Fadjarenie, Agustin (E-Jurnal Akuntansi, 2022)
The quality of financial reports can be seen through the characteristics adopted, several characteristics that can be assessed, namely the narcissism of the director, the composition of the independent commissioners and the gender of the director. The research objective is to obtain empirical evidence of the influence of director narcissism, composition of independent commissioners and director gender on the quality of financial reports. The research was conducted at companies listed on the Indonesia Stock Exchange for the period 2014 – 2019. The research sample consisted of 180 observations. Data is processed using multiple linear regression analysis. The results showed that the director's narcissism and the composition of the independent commissioners had an effect on the quality of financial reports, while there was no effect on the gender of directors and the quality of financial reports. Keywords: Narcissism Director; The Composition of Independent Commissioners; Gender Directors on the Quality of Financial Reports